Luminescent properties of Zn complexes based on tetradentate N2O2-donor pyrazolone schiff bases. (December 2020) - Gusev, Alexey; Shul'gin, Victor; Braga, Elena; Zamnius, Ekaterina; Kryukova, Mariya; Linert, Wolfgang
Abstract: A nine new Zn(II) complex were synthesized based on a new Salen-type tetradentate N2O2 ligands derived from 1-phenyl-3-methyl-4-formyl-5-pyrazolone. Complexes have been characterized by single-crystal X-ray diffraction, ESI-mass spectroscopy, elemental analysis, IR spectroscopy and thermal gravimetric analysis. UV–vis, emission and electrochemical studies indicated that changes of the electronic states of the diamine moieties are main parameter that influences the absorption and the emission color of the investigated zinc(II) complexes. Graphical abstract: Image 1 Highlights: Bright luminescence of Zn complexes with new Salen-type ligands based on pyrazolone schiff bases are studied. The nature of the bridge in the ligand scaffold was determined to be the main parameter that influences the. Emission color of the investigated zinc complexes.